Mathematical Problem-Solving Ability in Open-Ended Circle Problems: A Study Based on Students' Learning Interest - Annisa Febrianty; Feri Tiona Pasaribu; Duano Sapta Nusantara (Jurnal Inovasi Matematika, 2025)
This study aims to describe students' mathematical problem-solving abilities in solving open-ended problems related to the topic of circles, based on their learning interest. The research employs a descriptive qualitative approach, involving junior high school students from SMP Negeri 14 Kota Jambi, categorized into high, medium, and low levels of learning interest. Data were collected through questionnaires to measure students' learning interest, tests to assess problem-solving abilities, and interviews for in-depth exploration. The findings reveal that students with high learning interest successfully demonstrated all indicators of problem-solving ability, including understanding the problem, planning a solution, executing the plan, and re-checking the results. Students with medium learning interest faced difficulties in calculation and were unable to re-check their solutions. Meanwhile, students with low learning interest struggled to plan solutions, resulting in an inability to solve problems or verify their answers. These results highlight the critical role of learning interest in enhancing students' problem-solving abilities in mathematics, particularly in addressing open-ended problems.